Meta-Analysis of the Effect of High-Intensity Interval Training in Increasing High-Density Lipoprotein Levels in Type 2 Diabetes Mellitus Patients - Adelita, Sela Putri; Pamungkasari, Eti Poncorini; Murti, Bhisma (Indonesian Journal of Medicine, 2020)
Background: Diabetes mellitus is one of the second biggest health problems. The International Diabetes Federation said that diabetes currently affects 382 million people worldwide, with type 2 diabetes mellitus (DM) being the largest prevalence of 85-95% of the diabetes population. This study aimed to estimate the effect of high-intensity interval training (hiit) on increasing levels of high-density lipoprotein in patients with type 2 diabetes mellitus based on the results of several previous studies.Subjects and Method: This study was a meta-analysis and systematic study, with the following PICO Population =type 2 diabetes mellitus patients aged 35-65 years. Intervention=HIIT. Comparison = No HIIT. Outcome = increased levels of high-density lipoprotein. The articles used in this study were obtained from several databases, including PubMed, ScienceDirect, and Google Scholar. The keywords for finding articles were: "HIIT" OR "High-Intensity interval Training" OR "Diabetes Mellitus" OR "High-Density Lipoprotein" AND "Randomized Controlled Trial". The articles included in this study were full-text with a randomized controlled trial. Articles were analyzed by PRISMA flow chart and RevMan 5.3.Results: A total of 9 articles reviewed in this meta-analysis study originated from New York, Canada, France, Thailand, Berlin, Denmark, Australia, and the United Kingdom. Studies showed that high intensity interval training increased the levels of high density lipoproteins (Mean Difference= 0.01; 95% CI= 0.31 to 0.30; p= 0.970).Conclusion: High-intensity interval training increases high-density lipoprotein levels.Keywords: High-intensity interval training, type 2 diabetes mellitus, high-density lipoproteinCorrespondence: Sela Putri Adelita, Masters Program In Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: Selaadelita558@gmail.com.Indonesian Journal of Medicine (2020), 05(04): 272-281https://doi.org/10.26911/theijmed.2020.05.04.02.